(untitled) (Research, Society and Development, 2020)
Objective: To analyze the association of continuity of studies with socioeconomic, demographic, sexual variables, support after delivery. Method: Cross-sectional study with a quantitative approach carried out with adolescent pregnant women attended in primary health care in the municipality of São José do Rio Preto-SP, through a semi-structured questionnaire and Instrumental for Socioeconomic Evaluation. Correlational statistical analyzes (Pearson and Odds Ratio) were performed using the SPSS Statistics Software (version 19.0). Results: It was associated with the non-continuation of studies with pregnancy between the ages of 15 and 19, marital status, married or in a stable relationship, lower salary ranges, first relationship between 15 and 19 years, receiving support during pregnancy, fixed partner and relationship stable. Conclusion: It appears that socioeconomic, demographic, sexual and support variables after delivery interfere with the continuity of studies of pregnant adolescents.